Modulatory effects of curcumin on the atherogenic activities of inflammatory monocytes: Evidence from in vitro and animal models of human atherosclerosis. (24th December 2019) - Mohammadian Haftcheshmeh, Saeed; Karimzadeh, Mohammad R.; Azhdari, Sara; Vahedi, Parviz; Abdollahi, Elham; Momtazi‐Borojeni, Amir A.
Abstract: Atherosclerosis is a complex and long‐lasting disorder characterized by chronic inflammation of arteries that leads to the initiation and progression of lipid‐rich plaques, in which monocytes/macrophages play the central role in endothelial inflammation and taking up these lipids. Circulating monocytes can adopt a long‐term proinflammatory phenotype leading to their atherogenic activities. During atherogenic condition, inflammatory monocytes adhere to the surface of the activated endothelial cells and then transmigrate across the endothelial monolayer into the intima, where they proliferate and differentiate into macrophages and take up the lipoproteins, forming foam cells that derive atherosclerosis progression. Therefore, modulating the atherogenic activities of inflammatory monocytes can provide a valuable therapeutic approach for atherosclerosis prevention and treatment. Curcumin is a naturally occurring polyphenolic compound with numerous pharmacological activities and shows protective effects against atherosclerosis; however, underlying mechanisms are not clearly known yet. In the present review, on the basis of a growing body of evidence, we show that curcumin can exert antiatherosclerotic effect through inhibiting the atherogenic properties of monocytes, including inflammatory cytokine production, adhesion, and transendothelial migration, as well as intracellular cholesterol accumulation. Abstract : Curcumin inhibit atherogenic activities of monocytes mainly through modulating cholesterol efflux/influx (upper figure), suppressing transendothelial migration (bottom left corner figure), and inhibiting production of inflammatory cytokines (bottom right corner figure).